Revisiting doxycycline in pregnancy and early childhood – time to rebuild its reputation?. Issue 3 (3rd March 2016) - Cross, Ruby; Ling, Clare; Day, Nicholas P. J.; McGready, Rose; Paris, Daniel H.
ABSTRACT: Introduction: Doxycycline is highly effective, inexpensive with a broad therapeutic spectrum and exceptional bioavailability. However these benefits have been overshadowed by its classification alongside the tetracyclines – class D drugs, contraindicated in pregnancy and in children under 8 years of age. Doxycycline-treatable diseases are emerging as leading causes of undifferentiated febrile illness in Southeast Asia. For example scrub typhus and murine typhus have an unusually severe impact on pregnancy outcomes, and current mortality rates for scrub typhus reach 12-13% in India and Thailand. The emerging evidence for these important doxycycline-treatable diseases prompted us to revisit doxycycline usage in pregnancy and childhood. Areas Covered: A systematic review of the available literature on doxycycline use in pregnant women and children revealed a safety profile of doxycycline that differed significantly from that of tetracycline; no correlation between the use of doxycycline and teratogenic effects during pregnancy or dental staining in children was found. Expert Opinion: The change of the US FDA pregnancy classification scheme to an evidence-based approach will enable adequate evaluation of doxycycline in common tropical illnesses and in vulnerable populations in clinical treatment trials, dosage-optimization pharmacokinetic studies and for the empirical treatment of undifferentiated febrile illnesses, especially in pregnant women and children.